Using the Residual Network Module to Correct the Sub-Seasonal High Temperature Forecast - Jin, Wei; Zhang, Wei; Hu, Jie; Weng, Bin; Huang, Tianqiang; Chen, Jiazhen (Frontiers in Earth Science, 2022)
The high temperature forecast of the sub-season is a severe challenge. Currently, the residual structure has achieved good results in the field of computer vision attributed to the excellent feature extraction ability. However, it has not been introduced in the domain of sub-seasonal forecasting. Here, we develop multi-module daily deterministic and probabilistic forecast models by residual structure and finally establish a complete set of sub-seasonal high temperature forecasting system in the eastern part of China. The experimental results indicate that our method is effective and outperforms the European hindcast results in all aspects: absolute error, anomaly correlation coefficient and other indicators are optimized by 8%-50%, and the equitable threat score is improved by up to 400%. We conclude that the residual network has a sharper insight into the high temperature in sub-seasonal high temperature forecasting compared to traditional methods and convolutional networks, thus enabling more effective early warning of extreme high temperature weather.